Herd-level heterogeneity of antimicrobial resistance in commensal Escherichia coli: A nationwide high-throughput survey of Australian pig herds - Sam Abraham; David Jordan; Marin Milotic; Shewli Mukerji; Yvette Pollock; Samantha Sterndale; David J. Hampson; Kittitat Lugsomya; Rebecca Abraham (Veterinary Microbiology, 2026)

Spaced out: An economic framework to explore the impacts of PV panel spacing on large-scale farming in Colorado - Brian Mirletz; James McCall; Samantha Bryan; Dala Al Mukhaini; Claire Nguyen; Sam Anderson; Stephan Weiler; Jordan Macknick (Agricultural Systems, 2026)

Genomic analysis of a porcine exudative epidermitis outbreak caused by Staphylococcus hyicus - Alec Truswell; David Jordan; Stanley Pang; Tanya Cherrington; David J. Hampson; John Blinco; Sandy Adsett; Rebecca Abraham; Marc Stegger; Sam Abraham (Veterinary Microbiology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Antimicrobial resistance, genomic, and public health insights into Enterococcus spp. from Australian cattle - Rebecca Abraham; Shafi Sahibzada; Terence Lee; David Jordan; Kate McMillan; Glen Mellor; Lesley Duffy; Kittitat Lugsomya; Mark O'Dea; Sam Abraham; Robert Barlow (Veterinary Microbiology, 2026)

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

NextGen In A Box (NGIAB): Open-Source containerization of the NextGen framework to enable community-driven hydrology modeling - Arpita Patel; James Halgren; Zach Wills; Nels Frazier; Benjamin Lee; Joshua Cunningham; Jordan Laser; Mohammadsepehr Karimiziarani; Trupesh Patel; Giovanni Romero; Matthew Denno; Sam Lamont; et al. (Environmental Modelling & Software, 2025)

Patterns of transcriptomic aging in the hippocampus of rhesus macaques highlight midlife transitions - Tanner J. Anderson; Marina M. Watowich; Kenneth L. Chiou; Elisabeth A. Goldman; Sam Peterson; Jordan A. Anderson; Noah Snyder-Mackler; Lucia Carbone; Steven G. Kohama; Kirstin N. Sterner (GeroScience, 2025)
Patterns of brain aging are generally conserved among primates; however, there is marked variation in the observed rate among individuals, species, and brain regions. The hippocampus is a region particularly susceptible to the aging process. To better understand how the hippocampus changes over the lifespan, we measured gene expression in 96 banked hippocampus samples from adult male and female rhesus macaques aged 3–35 years old. Importantly, our dataset included representation across adulthood allowing us to characterize age-related patterns in gene expression during midlife, a period often underrepresented in studies of aging. We used autoregressive integrated moving average models to examine age-associated changes in gene expression to identify 2679 differentially expressed genes (FDR < 0.05) that fit four broad patterns of expression: linearly upregulated or downregulated across age, and two clusters with nonlinear patterns. Importantly, the nonlinear clusters highlight transitions in expression trajectories centered around ~ 10 years of age (~ 30 years of age in humans) indicating an important period that may have a critical impact on hippocampal aging. Changes in gene expression variance across age found that genes in individuals > 20 years of age (> 50 years of age in humans) have greater variance in expression than individuals aged 10–20 years (FDR < 0.05). Collectively, our results highlight molecular changes occurring during midlife which may shape brain aging in longer lived primates and may offer insight into increased susceptibility to neurodegenerative disease in humans.

Novel robotic tools used for the detection of faecal shedding of Escherichia coli resistant to critically important antimicrobials in healthy dogs - Breanna Knight; Alec Truswell; David Jordan; Amanda Ash; David J. Hampson; Sam Abraham (Veterinary Microbiology, 2025)

A Synthesis of Factors Related to Trends in Abundance and Demography of Alaska Chinook Salmon ( Oncorhynchus tshawytscha , Salmonidae): Implications for Research, Management, and Policy - Chase C. Lamborn; Jan Ohlberger; Timothy E. Walsworth; Peter A. H. Westley; Curry J. Cunningham; Sam Wynsma; Jordan W. Smith (Fish and Fisheries, 2025)
Across Alaska, there have been synchronous declines in the abundance, mean age, and size of Chinook salmon ( Oncorhynchus tshawytscha , Salmonidae), a species with immense social and ecological importance. The decline of Chinook salmon, and regulations addressing declines, have drastically impacted people who rely on Alaska's fisheries. Despite their importance, the drivers causing Chinook salmon declines are still not well understood. Therefore, to improve our understanding of the likely drivers of these large‐scale synchronous declines, we synthesised the peer‐reviewed Chinook salmon literature published between 2010 and 2024 using a weight‐of‐evidence approach. We identified 94 variables used to explain the trends in abundance and demographics of Chinook salmon. Each variable's association with trends in Chinook salmon was individually assessed and integrated using a standardised method. Results of this synthesis suggest the drivers for large‐scale synchronous declines have occurred in the North Pacific Ocean. Specifically, we found marine predation, size selective harvest, and pink salmon ( Oncorhynchus gorbuscha ) abundance are the factors most strongly associated with reduced size and age. Results also suggest ocean productivity–specifically winter sea surface temperature and the North Pacific Gyre Oscillation–are the most frequently identified predictors of regional Chinook salmon abundance. In addition to addressing freshwater factors like adult heat stress and juvenile predation, we suggest research, policy, and management focus on how to better understand and address the interactions between ocean productivity, marine predation, size selective harvest, and pink salmon abundance to improve the condition of Chinook salmon, and the people and ecosystems benefiting from them.

Current trends and biases in groundwater modelling using the community-driven groundwater model portal (GroMoPo) - Daniel Zamrsky; Sacha Ruzzante; Kyle Compare; Daniel Kretschmer; Sam Zipper; Kevin M. Befus; Robert Reinecke; Yara Pasner; Tom Gleeson; Kristen Jordan; Mark Cuthbert; Anthony M. Castronova; et al. (Hydrogeology Journal, 2025)
Groundwater, Earth’s largest nonfrozen freshwater reservoir, is vital for water supply security. Groundwater models help to manage complex domestic, agricultural, and industrial water demands while preserving ecosystem health under climate change. The community-driven groundwater model portal (GroMoPo) hosts groundwater model metadata to analyse biases and distribution of groundwater models. Over 450 models are currently featured on GroMoPo, with most models from high-GDP countries at local-to-regional scales. The GroMoPo initiative addresses current knowledge gaps and facilitates future collaboration and data sharing.

Proximity to human settlement is directly related to carriage of critically important antimicrobial-resistant Escherichia coli and Klebsiella pneumoniae in Silver Gulls - Shewli Mukerji; Shafi Sahibzada; Rebecca Abraham; Marc Stegger; David Jordan; David J. Hampson; Mark O’Dea; Terence Lee; Sam Abraham (Veterinary Microbiology, 2023)

A comprehensive genomic reporting structure for communicating all clinically significant primary and secondary findings - Jordan Sam; Emma Reble; Rita Kodida; Angela Shaw; Marc Clausen; Mariana Gutierrez Salazar; Salma Shickh; Chloe Mighton; June C. Carroll; Susan Randall Armel; Melyssa Aronson; José-Mario Capo-Chichi; et al. (Human Genetics, 2022)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Neolithic farmers or Neolithic foragers? Organic residue analysis of early pottery from Rakushechny Yar on the Lower Don (Russia) - Manon Bondetti; Lara González Carretero; Ekaterina Dolbunova; Krista McGrath; Sam Presslee; Alexandre Lucquin; Viktor Tsybriy; Andrey Mazurkevich; Andrey Tsybriy; Peter Jordan; Carl Heron; John Meadows; et al. (Archaeological and Anthropological Sciences, 2021)
The emergence of pottery in Europe is associated with two distinct traditions: hunter-gatherers in the east of the continent during the early 6th millennium BC and early agricultural communities in the south-west in the late 7th millennium BC. Here we investigate the function of pottery from the site of Rakushechny Yar, located at the Southern fringe of Eastern Europe, in this putative contact zone between these two economic ‘worlds’. To investigate, organic residue analysis was conducted on 120 samples from the Early Neolithic phase (ca. mid-6 th millennium BC) along with microscopic and SEM analysis of associated foodcrusts. The results showed that the earliest phase of pottery use was predominantly used to process riverine resources. Many of the vessels have molecular and isotopic characteristics consistent with migratory fish, such as sturgeon, confirmed by the identification of sturgeon bony structures embedded in the charred surface deposits. There was no evidence of dairy products in any of the vessels, despite the fact these have been routinely identified in coeval sites to the south. Further analysis of some of the mammalian bones using ZooMS failed to demonstrate that domesticated animals were present in the Early Neolithic. Nevertheless, we argue that intensive exploitation of seasonally migratory fish, accompanied by large-scale pottery production, created storable surpluses that led to similar socio-economic outcomes as documented in early agricultural societies.

First complete genome sequence of carnation latent virus, the type member of the genus Carlavirus - Ramon Jordan; Erica Korolev; Sam Grinstead; Dimitre Mollov (Archives of Virology, 2021)

Beyond medically actionable results: an analytical pipeline for decreasing the burden of returning all clinically significant secondary findings - Emma Reble; Mariana Gutierrez Salazar; Kathleen-Rose Zakoor; Sam Khalouei; Marc Clausen; Rita Kodida; Salma Shickh; Chloe Mighton; Iris Cohn; Kasmintan A. Schrader; Raymond H. Kim; Jordan Lerner-Ellis; et al. (Human Genetics, 2021)

Chemoprevention of Breast Cancer: Current and Future Prospects - Sam G. Pappas; V. Craig Jordan (Cancer and Metastasis Reviews, 2002)